The 2007 subprime market crisis through the lens of European Central Bank auctions for short-term funds - Nuno Cassola; Ali Hortacsu; Jakub Kastl (European Central Bank (ECB), 2011)
We study European banks' demand for short-term funds (liquidity) during the summer 2007 subprime market crisis. We use bidding data from the European Central Bank's auctions for one-week loans, their main channel of monetary policy implementation. Our analysis provides a high-frequency, disaggregated perspective on the 2007 crisis, which was previously studied through comparisons of collateralized and uncollateralized interbank money market rates which do not capture the heterogeneous impact of the crisis on individual banks. Through a model of bidding, we show that banks' bids reflect their cost of obtaining short-term funds elsewhere (e.g., in the interbank market) as well as a strategic response to other bidders. The strategic response is empirically important: while a naïve interpretation of the raw bidding data may suggest that virtually all banks suffered an increase in the cost of short-term funding, we find that for about one third of the banks, the change in bidding behavior was simply a strategic response. We also find considerable heterogeneity in the short-term funding costs among banks: for over one third of the bidders, funding costs increased by more than 20 basis points, and funding costs vary widely with respect to the country-of-origin. Estimated funding costs of banks are also predictive of market- and accounting-based measures of bank performance, suggesting the external validity of our findings.
Keywords: D44; E58; G01; 330; liquidity crisis; Multiunit auctions; primary market; structural estimation; subprime market